Raspberry Pi projects for kids : start your own coding adventure with your kids by creating cool and exciting games and applications on the Raspberry Pi /: start your own coding adventure with your kids by creating cool and exciting games and applications on the Raspberry Pi. (2014) - (Computer science researcher), Bates, Daniel
No abstract available